A System Modelling Approach to Assessment of Hybrid Water Supply Solutions in eThekwini Municipality - McKune, Danica (Department of Civil Engineering, 2022)
Water security in South Africa is a major concern, particularly in the context of urbanisation, the concomitant increases in water demand, and the potential for climate change to aggravate water shortages. Provision of basic services remains a significant challenge. Improving economic and social equity, vitally supported by adequate water supply and water quality, while ensuring environmental sustainability (maintaining water resources requires healthy ecosystems) is the dual challenge facing South Africa. There is growing recognition of the need for alternative approaches to water management, such as Sustainable Urban Water Management (SUWM). Decentralisation and integration to allow consideration of the total water cycle are fundamental themes of the SUWM paradigm. There is theoretical and experiential evidence that the current infrastructure archetype (of conveying a particular water stream from origin to destination by the most efficient means) could benefit from inclusion of such principles. SUWM is purported to have three core benefits: (1) A more natural water cycle, (2) Improved water security through diversification of sources, and (3) Resource efficiency. A complete transition to alternative water provision models is neither economical nor practically feasible in already developed areas, necessitating innovations in new areas and as retrofits to existing systems; systems where the water services configuration is evolving in this way are termed hybrid systems. Alternative water provision models bring dynamic changes to existing systems which may not be intuitive: the complexity of urban water systems and the resulting uncertainty means an intervention may achieve one SUWM objective yet undermine another. Thorough evaluations of alternative water provision models are therefore essential, while recognising that less learned experience on the performance of innovative solutions means uncertainty remains part of the evaluation. This research therefore aims to contribute to the theoretical body of knowledge on the net system effects of integrated management of the water cycle where alternative and decentralised solutions are introduced to existing systems. The overarching research objective was therefore application of an assessment framework, which was underpinned by the development of a systems dynamics model in GoldSim software. The systems dynamics model has been tailored for application to the selected case study area – eThekwini Municipality in South Africa. Akin to most South African cities, this region is home to a diverse range of consumers (fully serviced urban suburbs, informal settlements, peri-urban settlements, and rural areas), is experiencing urbanisation and growth in demand, and is supplied by catchments whose water resources are fully developed and are at risk of becoming significantly stressed. This is set against a backdrop of challenges in service delivery, environmental concerns as a result of water practices, potential impacts of climate change in the future, and ultimately sustainability of service provision. The developed systems dynamics model is a macro-scale integrated flow model, capable of assessing implementation of water servicing scenarios (specifically any combination of Water Conservation and Water Demand Management, rainwater harvesting, stormwater harvesting, groundwater use, greywater reuse, wastewater recycling, and desalination) at a regional level. Monte Carlo analyses were carried out to test system sensitivity to uncertainty in particular parameters. Of the possible interventions, five scenario paths were assessed: (1) Baseline, or “business as usual”, (2) WCWDM, (3) rainwater harvesting and real loss reduction, (4) greywater reuse and WCWDM, and (5) wastewater recycling and real loss reduction. Considered against the three core benefits of SUWM, each of the intervention scenarios yielded positive results. The developed model proved valuable in the scoping of SUWM interventions, and understanding the system-wide effects SUWM interventions may have on the water cycle. Such systems modelling approaches may therefore be considered to provide the framework and parameters within which further detailed and project-specific hydraulic and contaminant transport analysis could take place.